2014
DOI: 10.1093/ejcts/ezu045
|View full text |Cite
|
Sign up to set email alerts
|

EuroSCORE II with SYNTAX score to assess risks of coronary artery bypass grafting outcomes

Abstract: The combination of EuroSCORE II and SYNTAX score was useful in predicting early major complications after CABG. In the long term, EuroSCORE II continued to be associated with late mortality, but SYNTAX score did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
11
1
2
Order By: Relevance
“…SYNTAX score predicts short- and long-term adverse events following revascularization 23). Although, SYNTAX score predicts early adverse events in patients undergoing off-pump CABG, there was no significant difference between a higher SYNTAX score and development of POAF 24). Our study design was conducted with on-pump coronary artery bypass graft surgery patients due to a lower incidence of AF in patients undergoing off-pump surgery 25)…”
Section: Discussionmentioning
confidence: 99%
“…SYNTAX score predicts short- and long-term adverse events following revascularization 23). Although, SYNTAX score predicts early adverse events in patients undergoing off-pump CABG, there was no significant difference between a higher SYNTAX score and development of POAF 24). Our study design was conducted with on-pump coronary artery bypass graft surgery patients due to a lower incidence of AF in patients undergoing off-pump surgery 25)…”
Section: Discussionmentioning
confidence: 99%
“…Gecmen et al [34] also found that higher SYNTAX scores were related to more frequent PoAF in patients undergoing isolated on-pump CABG. Contrary to this finding, Fukui et al [35] found no significant difference between high and low SYNTAX score groups for the development of PoAF in patients undergoing off-pump CABG. In our study, CSS integrating the angiographic findings with clinical variables such as advanced age, left ventricular dysfunction and renal impairment, which were wellknown risk factors for the occurrence of PoAF after CABG, was superior to the SS in predicting PoAF.…”
Section: Discussionmentioning
confidence: 78%
“…Por ejemplo, se ha valorado su aplicación en procedimientos de revascularización coronaria percutánea 292 , aunque los resultados son poco claros. Parece que al combinar el Euroscore con el modelo SYNTAX, modelo que sirve para estratificar el riesgo de los pacientes que van a ser sometidos a revascularización percutánea y que se basa en la anatomía de las coronarias, la predicción obtenida mejoraba con respecto a la predicción obtenida solo con el modelo SYNTAX 212,213,293 . También se ha intentado añadir al Euroscore características específicas de los pacientes coronarios, como lesión de TCI o lesión de tres vasos, obteniéndose buenos resultados 214 .…”
Section: Escalas De Gravedad Utilizadas En Cirugiaunclassified